The Relationship Between Stress Levels and Coping Mechanisms in Students Facing Clinical Practice - Izzati Aufa, Nurul; Nopianti, Risna; Indira, Saranova; Nurfadilah, Rizki; Febrianti, Selvi (Yayasan Inspirasi El Burhani, 2024)
Introduction: Clinical practice is a critical stage in nursing education but often causes considerable stress among students. Coping mechanisms play an essential role in managing this stress and determining students’ academic and psychological outcomes. Methods: A cross-sectional study was conducted in May 2024 at STIKes Muhammadiyah Ciamis with 34 students in clinical practice (PBK). Peer support (independent variable) was measured using a validated questionnaire with four indicators (Cronbach’s alpha = 0.84). Stress levels (dependent variable) were assessed using the 14-item stress subscale of the DASS-42 (Cronbach’s alpha = 0.89). Data were collected via Google Forms and analyzed with SPSS 29 using descriptive statistics and the Chi-square test (p < 0.05). Results: The results showed that most students experienced moderate stress (76.5%) and the rest experienced severe stress (23.5%). No participants reported mild stress levels. In terms of coping mechanisms, 79.4% of students used adaptive coping strategies, while 20.6% used maladaptive ones. The Chi-square test indicated no statistically significant relationship between stress levels and the type of coping mechanisms used (p = 0.465). Conclusion: This study found no significant association between stress levels and coping mechanisms among undergraduate students undergoing clinical learning. Although most students experienced moderate to severe stress, the majority employed adaptive coping strategies. These findings suggest a promising level of resilience among students and highlight the importance of continuous institutional support and coping-skills development in clinical education settings.